Mass Media Support to Rural Women for Maternal Health Development - A Study in Dhubri District of Assam - Choudhury, Arupjyoti; Barman, Arpana (Journal of Advanced Research in Journalism & Mass Communication, 2019)
The main function of mass media is to inform and educate people. Maternal health of pregnant women is not only influenced by availability, accessibility of health care services but also by access to information about care during pregnancy. Due to limited exposure of rural women to mass media, information related to mass media are not able to reach the poor and illiterate women. Socio-economic background of rural women is also statistically significant in seeking benefits from the mass media. Mass media must facilitate in creating desire among poor rural women in seeking more and more information on maternal health for the development of women’s health. Integrated approach by various grass root level community development programs must be undertaken to enable rural women’s access to mass media for information related to their development. How to cite this article: Choudhury A, Barman A. Mass Media Support to Rural Women for Maternal Health Development - A Study in Dhubri District of Assam. J Adv Res Jrnl Mass Comm 2019; 6(2): 12-17.